Economic and legal responsibility: signs, of procedure - Мілімко, Лариса Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The article deals with the issue of signs and procedures for the application of economic and legal responsibility. The attention that the economic and legal responsibility has the following features: the actual basis of economic and legal responsibility is a fact of contractual or non-contractual tort offense; depending on different legal grounds liability arising from an act of law, contract, administrative act; it is aimed at a person or property status of the offender, which is the subject of economic relations; the scope of economic and legal responsibility is the sphere of management; occurs in the presence of the offense, but different from the traditional structure; sanctions (penalties) affect the economic interests of the offender. These features distinguish economic liability from civil and administrative liability. Procedures for the use of economic and legal responsibility of a few: - Litigation or court order; - Direct lender promptly; - Special - authorized state authority or local government.